World’s First 24/7 Mobile Stroke Unit: Initial 6-Month Experience at Mercy Health in Toledo, Ohio - Lin, Eugene; Calderon, Victoria; Goins-Whitmore, Julie; Bansal, Vibhav; Zaidat, Osama (Frontiers in Neurology, 2018)
Background and purpose As the fourth mobile stroke unit (MSU) in the nation, and the first 24/7 unit worldwide, we review our initial experience with the Mercy Health MSU and institutional protocols implemented to facilitate rapid treatment of acute stroke patients and field triage for patients suffering other time-sensitive, acute neurologic emergencies in Lucas County, Ohio, and the greater Toledo metropolitan area. Methods Data was prospectively collected for all patients transported and treated by the MSU during the first 6 months of service. Data was abstracted from documentation of on-scene emergency medical services (EMS) personnel, critical care nurses, and onboard physicians, who participated through telemedicine. Results The MSU was dispatched 248 times and transported 105 patients after on-scene examination with imaging. Intravenous (IV) tissue plasminogen activator (tPA) was administered to 10 patients; 8 patients underwent successful endovascular therapy after a large vessel occlusion was identified using CT performed within the MSU without post treatment symptomatic hemorrhage. Moreover, 14 patients were treated with IV anti-epileptics for status epilepticus, and 19 patients received IV anti-hypertensive agents for malignant hypertension. MSU alarm to on-scene times and treatment times were 34.7 min (25–49) and 50.6 min (44.4–56.8), respectively. Conclusion The world’s first 24/7 MSU has been successfully implemented with IV-tPA administration rates and times comparable to other MSUs nation-wide, while demonstrating rapid triage and treatment in the field for neurologic emergencies, including status epilepticus. With the rising number of MSUs worldwide, further data will drive standardized protocols that can be adopted nationwide by EMS.